Sperm morphology and performance in relation to postmating prezygotic isolation in two recently diverged passerine species - Poignet, Manon; Baránková, Lucie; Reif, Jiří; Stopka, Pavel; Stopková, Romana; Frolikova, Michaela; Cramer, Emily R A; Johnsen, Arild; Kverek, Pavel; Osiejuk, Tomasz S; Komrskova, Katerina; Albrecht, Tomáš; et al. (Scientific reports, 2022)
Divergence in sperm phenotype and female reproductive environment may be a common source of postmating prezygotic (PMPZ) isolation between species. However, compared to other reproductive barriers it has received much less attention. In this study, we examined sperm morphology and velocity in two hybridizing passerine species, the common nightingale (Luscinia megarhynchos) and thrush nightingale (L. luscinia). In addition, we for the first time characterized a passerine female reproductive tract fluid proteome. We demonstrate that spermatozoa of the common nightingale have significantly longer and wider midpiece (proximal part of the flagellum containing mitochondria) and longer tail compared to spermatozoa of thrush nightingale. On the other hand, they have significantly shorter and narrower acrosome. Importantly, these differences did not have any effect on sperm velocity. Furthermore, the fluid from the reproductive tract of common nightingale females did not differentially affect velocity of conspecific and heterospecific sperm. Our results indicate that the observed changes in the flagellum and acrosome size are unlikely to contribute to PMPZ isolation through differential sperm velocity of conspecific and heterospecific sperm in the female reproductive tract. However, they could affect other postcopulatory processes, which might be involved in PMPZ isolation, such as sperm storage, longevity or sperm-egg interaction.
Keywords: rozmnožování; Reproduction; spermie; Insemination; sperma; Songbirds; Spermatozoa; Male; Semen; Animals; Female; mužské pohlaví; ženské pohlaví; zpěvní ptáci; zvířata; inseminace